2020
DOI: 10.1021/acsomega.0c02212
|View full text |Cite
|
Sign up to set email alerts
|

Simple Sonochemical Method to Optimize the Heating Efficiency of Magnetic Nanoparticles for Magnetic Fluid Hyperthermia

Abstract: We developed a fast, single-step sonochemical strategy for the green manufacturing of magnetite (Fe 3 O 4 ) magnetic nanoparticles (MNPs), using iron sulfate (FeSO 4 ) as the sole source of iron and sodium hydroxide (Na(OH)) as the reducing agent in an aqueous medium. The designed methodology reduces the environmental impact of toxic chemical compounds and minimizes the infrastructure requirements and reaction times down to minutes. The Na(OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…The magnetic characterization reveals that the studied sample exhibit a standard ferromagnetic character [33]. Likewise, the saturation magnetization M S value of 70.64 emu•g −1 and the coercivity value of 2.31 Oe are in close agreement with previous reports on magnetite [33,34]. In addition, the morphology of the synthesized Fe 3 O 4 nanoparticles was investigated by using the transmission electron microscopy (TEM).…”
Section: Characteristics Of the Free-standing Magnetite Nanoparticlessupporting
confidence: 87%
“…The magnetic characterization reveals that the studied sample exhibit a standard ferromagnetic character [33]. Likewise, the saturation magnetization M S value of 70.64 emu•g −1 and the coercivity value of 2.31 Oe are in close agreement with previous reports on magnetite [33,34]. In addition, the morphology of the synthesized Fe 3 O 4 nanoparticles was investigated by using the transmission electron microscopy (TEM).…”
Section: Characteristics Of the Free-standing Magnetite Nanoparticlessupporting
confidence: 87%
“…Nevertheless, the authors concluded that the magnetic characteristics of the nanoparticles obtained were lower than that of nanoparticles produced without ultrasound assistance due to the size difference. Fuentes-García and co-authors [ 69 ] developed a fast, single-step sonochemical strategy for the green manufacturing of magnetite nanoparticles, using iron sulfate as the sole source of iron and sodium hydroxide as the reducing agent in an aqueous medium. They reported that the sodium hydroxide concentration was varied to optimize the final size and magnetic properties of the magnetite nanoparticles and to minimize the number of corrosive byproducts from the reaction.…”
Section: Synthesis and Characterization Of Magnetite Nanoparticlesmentioning
confidence: 99%
“…The particle can be transformed into a highly crystalline form by subjecting them to higher temperature, following the sonochemical synthesis [53]. A cube-like Fe 3 O 4 nanoparticle with different particle sizes ranging from 20 to 58 nm was obtained by varying the molar concentration of the precursor and the reducing agent [54]. According to the LaMer model, the local supersaturation should be higher to achieve the smaller particles.…”
Section: Synthesis and Surface Functionalization Of Iron Oxidesmentioning
confidence: 99%